Fundamental Of Entrepreneurship (ENT300) : M.A.M.A. Food Truck / Mohammad Gadaffi Abdul Murad … [et al.] - Abdul Murad, Mohammad Gadaffi; Karim, Mohd Nuralmatusolehin; Abang Abdul Razak, Abang Akmal ‘Irfan; Abang Idham, Abang Muhammad Irfan (2017)
M.A.M.A. FOOD TRUCK is our business name .This food truck business seems very unfamiliar in this Kota Samarahan area. That's our main reason to came up with this food truck business. M.A.M.A. FOOD TRUCK is offering people a good quality ofwetern food along with complete nutrient for body. Our food truck offering western food with reasonable price The reason behind that is we want everyone can afford to buy our products. Other than that, with this food truck, we are trying to make our customer easier by showing concept “food will find you not you find the food"